Protection in Inheritance Relationships: Theoretical Issue - Pecheniy, Oleg; Dolgopolova, Liubov (Teisė, 2022)
This article explores the theoretical construction of civil rights protection in hereditary legal relations. Authors substantiate the use of both general and special ways of protection in the field of inheritance. Taking into account the requirements of judicial practice, the peculiarities of general protection methods in their extrapolation to inheritance law (recognition of rights, vindication of inherited property, etc.).
Keywords: inheritance law; protection of civil rights; ways of protection; hereditary relationship; heirs; invalidity of the will; theory of hereditary legal relations; methodology